Strictly ballroom [videorecording (DVD)] - Luhrmann, Baz; Mercurio, Paul; Morice, Tara; Hunter, Bill, 1940-2011 (Miramax Home Entertainment ; Distributed by Buena Vista Home Entertainment, 2002)
A championship ballroom dancer who's breaking all the rules and his ugly duckling dancing partner make their dreams come true together.